Optimizing propagation techniques and timing for pecan (Carya illinoinensis) under Poonch condition of Jammu region - KUMAR, NAVEEN; SHARMA, ARTI; LANZES, TSERING; JASROTIA, AMIT; BHAT, DEEP JI; MIR, MUZAFAR; DAS, SUSMITA (The Indian Journal of Agricultural Sciences, 2025)
The present experiment was carried out during 2021–22 at Krishi Vigyan Kendra-Poonch, Sher-e-Kashmir University of Agricultural Sciences and Technology, Jammu, Jammu and Kashmir with the objective to determine the technique and time of propagation in pecan (Carya illinoinensis Wangenh). The experiment was laid down in randomized complete block design (RCBD) with three replications. The results of the present study indicated that effects of propagation techniques and timing had a significant influence on graft take success, days to first bud burst, survival percent, plant height and number of shoot/plant, number of leaves/plant, rootstock diameter, plant spread N-S and E-W, total plant biomass. Out of different propagation techniques and timings, viz. whip grafting and four flap grafting in 2nd week of February and March, respectively patch budding and ring budding in 2nd week of July and August, respectively. The patch budding performed in August emerged as the most successful method, yielding the highest graft success (63.29%), and early bud sprouting (18.00 days), while whip grafting in March excelled in vegetative parameters, including plant height (55.20 cm), plant spread [N-S (49.00 cm), E-W (57.67 cm)], leaf count (57.33), rootstock diameter (0.66 cm), and biomass (121.00 g). Four flap grafting in February exhibited lower success rates (31.62%) and slower growth. These findings underscore the importance of selecting appropriate grafting methods and timings to optimize pecan propagation under varying climatic conditions, aiming to enhance productivity and quality in commercial cultivation practices.